Attenuation of Pancreatic Cancer In Vitro and In Vivo via Modulation of Nrf2 and NF-κB Signaling Pathways by Natural Compounds - Marta Cykowiak; Robert Kleszcz; Małgorzata Kucińska; Jarosław Paluszczak; Hanna Szaefer; Adam Plewiński; Hanna Piotrowska-Kempisty; Marek Murias; Violetta Krajka-Kuźniak (Cells, 2021)
Pancreatic cancer is a disease in which deregulation of signaling pathways plays a key role, thus searching for their novel modulators is a promising therapeutic strategy. Hence, in this study, the effect of phytochemical combinations on the canonical and non-canonical activation of Nrf2 and its interaction with the NF-κB pathway was evaluated in extensively proliferating pancreatic cancer cell line, PSN-1, in comparison to non-cancerous MS1 cells. The activation of Nrf2 and NF-κB, expression of their target genes, and effect on cell survival were assessed in PSN-1 cells. The tumor burden was evaluated in mice carrying xenografts. PSN-1 cells were more sensitive to the tested compounds as compared to the MS1 cell line. Combination of xanthohumol and phenethyl isothiocyanate was more effective than single compounds at decreasing the canonical and non-canonical activation of Nrf2 in PSN-1 cancer cells. Decreased activation of NF-κB, and subsequent reduced cytosolic COX-2 and nuclear STAT3 level indicated their anti-inflammatory and pro-apoptotic activities. In vivo studies showed the partial response in groups treated with xanthohumol or the combination of xanthohumol and phenethyl isothiocyanate. Overall, these results suggest that the combination of xanthohumol and phenethyl isothiocyanate may be a promising therapeutic candidate against pancreatic cancer.